Procedures for conducting usability evaluation experiment using eye tracker: a case study of Tobii T60 / Mohd Khairul Azwan Zaini - Azwan Zaini, Mohd Khairul (2011)
This research focuses on the procedures for conducting Usability Evaluation experiment using the Tobii T60 eye tracker. The aim of this research is to produce a multimedia-based tutorial that provides a set of guided instructions for conducting usability evaluation experiment using Tobii T60 eye tracker. The first objective is to acquire skills to use Tobii T60 eye tracker and conduct usability evaluation experiment. The second objective is to develop a set of guided instructions for conducting usability evaluation experiment using Tobii T60 eye tracker. Last but not least, the third objective is to demonstrate a multimedia-based tutorial for conducting usability experiment using Tobii T60 eye tracker. Fo*r achieving the deliverables of these three objectives acquire to follow the research methodology. There are five phases which are preliminary stage, preparation stage, data collection stage, data analysis stage and lastly writing report stage. Throughout this research, by involved in usability evaluation experiments and the result is producing a set of guided instructions for conducting usability evaluation experiment using Tobii T60 eye tracker.